Role of Social Studies Teacher to Inculcate Student Character Values - Ali Miftakhu Rosyad; Jajat Sudrajat; Siow Heng Loke (International Journal of Science Education and Cultural Studies, 2022)
This study aims to investigate the role of social science subject teachers in instilling character values ​​in students through the process of teaching and learning activities. This study used a quantitative approach with a case study type conducted at SMP Muhammadiyah Indramayu. The results of the study show that teachers of the Social Sciences subject at SMP Muhammadiyah Indramayu have tried their best to carry out their duties, especially in instilling historical awareness as well as values ​​of nationalism, identity and character in their students. This is proven when the writer observes while teaching in class being able to use strategies, various methods and modes so that the classroom atmosphere is lively and full of enthusiasm and is able to develop students to think historically analytically with various assignments. Besides that, teachers outside the classroom always monitor the character and attitudes of students to measure the extent to which what has been taught has an effect.